1999
DOI: 10.1111/j.1469-7793.1999.0527m.x
|View full text |Cite
|
Sign up to set email alerts
|

F‐actin stabilization increases tension cost during contraction of permeabilized airway smooth muscle in dogs

Abstract: Dynamic actin reorganization involving actin polymerization and depolymerization may play an important functional role in smooth muscle. This study tested the hypothesis that F‐actin stabilization by phalloidin increases tension cost (i.e. ATP hydrolysis rate per unit of isometric force) during Ca2+‐induced activation of Triton X‐100‐permeabilized canine tracheal smooth muscle. Adenosine 5′‐triphosphate (ATP) hydrolysis rate was quantified using an enzyme‐coupled NADH fluorometric technique, regulatory myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 43 publications
(90 reference statements)
9
64
0
Order By: Relevance
“…Previous studies of smooth muscle cells and tissues have shown that stimulation with contractile agonists initiates the polymerization of actin, and that this actin polymerization is required for tension development (6,7,9,12,16). Our studies suggest that this pool of actin is relatively small in differentiated muscle tracheal muscle tissues, probably less than 15% of the total pool of cellular actin (9,38).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies of smooth muscle cells and tissues have shown that stimulation with contractile agonists initiates the polymerization of actin, and that this actin polymerization is required for tension development (6,7,9,12,16). Our studies suggest that this pool of actin is relatively small in differentiated muscle tracheal muscle tissues, probably less than 15% of the total pool of cellular actin (9,38).…”
Section: Discussionmentioning
confidence: 82%
“…The contraction of smooth muscle tissues and cells causes an increase in the pool of filamentous (F) actin and a decrease in the pool of monomeric (globular) (G) actin (12,27,48,65,68,72,84,120,130,143). These transitions in the state of actin have been documented in diverse smooth muscle cell and tissue types using a number of different approaches to estimate monomeric and filamentous pools of actin.…”
Section: A Small Proportion Of Total Actin Undergoes Polymerization Dmentioning
confidence: 99%
“…These transitions in the state of actin have been documented in diverse smooth muscle cell and tissue types using a number of different approaches to estimate monomeric and filamentous pools of actin. These include the use of DNase inhibition assays to measure the amount of globular (G) actin (84), measurements of soluble (G) actin and insoluble (F) actin by cell fractionation (104,120,127,143), fluorescence imaging to visualize G-and F-actin in isolated smooth muscle cells or tissues using G-and F-actin-specific stains (27,48,68,72,130), assessments of the rate of ADP-ATP actin monomer exchange (12), and electron microscopic studies that quantify actin filament density (65). All of these approaches have consistently shown that an increase in F-actin and a decrease in G-actin occurs when smooth muscle cells or tissues are activated by a contractile stimulus.…”
Section: A Small Proportion Of Total Actin Undergoes Polymerization Dmentioning
confidence: 99%
“…Studies performed primarily in tracheal smooth muscle indicate that remodeling of the actin cytoskeleton is required for the full development of force induced by stimulation with contractile agonists (94,113,183). The process involves increased polymerization of actin, tyrosine phosphorylation of paxillin, the activation of the small GTP-binding proteins Rho and Cdc42, and conformational changes within focal adhesion sites involving specific focal adhesion proteins (161,164,180,181).…”
Section: Reviewsmentioning
confidence: 99%